Suppression of Cellular Immune Response in Spodoptera litura (Lepidoptera: Noctuidae) Larvae by Endophytic Fungi Nigrospora oryzae and Cladosporium uredinicola. (1st May 2014) - Thakur, Abhinay; Singh, Varinder; Kaur, Amarjeet; Kaur, Sanehdeep
Abstract: Endophytic fungi are a group of microbial plant symbionts that occur in living tissues of plants without causing visible disease symptoms. The mechanism underlying the anti-insect properties of endophytes is mainly attributed to the production of various alkaloid-based defensive compounds. The current study reveals the cytotoxic effects of endophytic Nigrospora oryzae- and Cladosporium uredinicola- infected cauliflower plants on larval hemocytes of Spodoptera litura (F.). Larvae fed on leaves of endophyte-infected plants exhibited abnormalities such as change in shape, extensive vacuolization, and necrosis in significantly higher percentage of hemocytes. The percentage of abnormal hemocytes increased with increase in feeding duration. The cytotoxic effect of endophytic fungi on the hemocytes ultimately leads to adverse effects on survival and fitness of the insect.